Protective Effects of Caffeic Acid Phenetyl Ester (Cape) on Exposure of Cigarette Smoke-induced Histological Changes in Rat Lung - Pekmez, Hıdır; Sönmez, M. Fatih; Kuş, İlter; Türkoğlu, Aslı Özdem; Ögetürk, Murat; Ozan, Enver; Sarsılmaz, Mustafa (Fırat University, 2003)
Aim: The aim of this study was to investigate the histological changes in lung of rats exposed to cigarette smoke and effects of caffeic acid phenetyl ester (CAPE) on these changes. Materials and method: For this purpose, 21 male Wistar rats were divided into three groups. Animals in Group I were used as control. Rats in Group II were exposed to cigarette smoke and rats in Group III were exposed to cigarette smoke and injected daily with CAPE. At the end of the 60-days experimental period, all rats were killed by decapitation. Following routine histological procedures, lung tissue specimens were examined under a light microscope. Results: In our study, quite intensive inflamatuar cell infiltration on wall of terminal bronchiol and interalveolar connective tissue was observed in the lung specimens of rats exposed to cigarette smoke. Additionally, it was seen that numerous macrophage containing hemosiderin pigment, vacuolization and congestion areas. In rats exposed to cigarette smoke and injected with CAPE, cigarette smoke-induced histological changes were partially disappeared. Conclusion: it was observed that exposure of cigarette smoke caused histological damage in lung tissue of rats and this damage was partially prevented by administration of CAPE.

Amaç: Bu çalışmada, sigara dumanına maruz kalan sıçanlara ait akciğerlerde meydana gelen histolojik değişikliklerin incelenmesi ve bu değişiklikler üzerine kafeik asit fenetil ester (CAPE)'in etkisinin araştırılması amaçlandı. Gereç ve yöntem: Bu amaçla 21 adet Wistar cinsi erkek sıçan üç gruba ayrıldı. Grup I'deki sıçanlar kontrol grubu olarak kullanıldı. Grup II'deki sıçanlar sigara dumanına maruz bırakıldı. Grup III'deki sıçanlara ise sigara dumanı maruziyeti ile birlikte günlük olarak CAPE enjekte edildi. 60 günlük deney süresi sonunda tüm sıçanlar dekapitasyonla öldürüldü. sıçanlardan alınan akciğer doku örnekleri rutin histolojik prosedürlerden geçirilerek ışık mikroskobunda incelendi. Bulgular: Çalışmamızda, sigara dumanına maruz bırakılan sıçanlara ait akciğerlerin ışık mikroskobik incelemesinde, terminal bronşiol duvarında ve alveoller arası bağ dokuda oldukça yoğun yangısal hücre infiltrasyonunun meydana geldiği gözlendi. Ayrıca hemosiderin pigmenti yüklü çok sayıda makrofaj, yer yer vakuolizasyon ve kanama alanları tespit edildi. Sigara maruziyeti ile birlikte CAPE uygulanan sıçanlarda ise, sigara maruziyetinin neden olduğu histolojik değişikliklerin kısmen kaybolduğu gözlendi. Sonuç: Sigara dumanına maruz bırakılan sıçanların akciğer dokusunda histolojik olarak hasarın meydana geldiği ve bu hasarın CAPE uygulaması ile kısmen önlendiği görüldü.
Sıçan Akciğerinde Sigara Maruziyeti ile Oluşan Histolojik Değişiklikler Üzerine Kafeik Asit Fenetil Ester (Cape)'in Koruyucu Etkisi